Profil Kemampuan Representasi Matematis Siswa Kelas VII Dalam Menyelesaikan Soal Penyajian Data - Hasanah, Farisatul; Handayani, Ucik Fitri (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2025)
This study aims to describe the profile of mathematical representation ability of seventh grade students in solving data presentation problems at Sultan Agung Islamic Junior High School Sudimoro, Malang Regency. This research used descriptive qualitative method involving seventh grade students in the 2024/2025 academic year. Data were collected through written test instruments that included indicators of verbal, symbol, and image representation abilities. The research subjects consisted of 3 students who represented each category of mathematical ability, namely high, medium and low. The results showed that students' verbal and symbol representation skills were very good, reaching a percentage of 91% and 86% respectively. However, the ability of image representation is still lacking because it only reaches a percentage of 45%. Difficulties in image representation are caused by limited understanding of the importance of visual representation in mathematics. students with high mathematical ability can fulfill all indicators of representation ability, namely verbal representation, symbols and images according to their abilities. Students with medium ability can only fulfill two indicators of representation ability, namely symbol and image representation according to their abilities. Students with low mathematical ability have not been able to fulfill all indicators of mathematical representation ability. This study suggests the need for additional practice and teaching to improve students' image representation skills in presenting and analyzing data effectively.